A Simple Method for Analysing Daily Rainfall Data a Case Study for Kota Bharu - Hassan, Mohamad Nooh; Stern, Rogern N. (1988)
It is demonstrated that a comprehensive analysis of rainfall data to give useful agronomic results should use the daily measurements. Simple methods of analysis are described and are illustrated using daily rainfall records of 34 years (1951-84) for Kota Bharu ini the north-eastern state of Kelantan.